Dynamic microscopic study of pre-equilibrium giant resonance excitation and fusion in the reactions 132Sn + 48Ca and 124Sn + 40Ca - Oberacker, V. E.; Umar, A. S.; Maruhn, J. A.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2012)
We study pre-equilibrium giant dipole resonance (GDR) excitation and fusion in the neutron-rich system 132Sn + 48Ca at energies near the Coulomb barrier, and we compare photon yields and total fusion cross sections to those of the stable system 124Sn + 40Ca. The dynamic microscopic calculations are carried out on a three-dimensional lattice using both the time-dependent Hartree-Fock (TDHF) method and the density-constrained TDHF method. We demonstrate that the peak of the GDR excitation spectrum occurs at a substantially lower energy than expected for an equilibrated system, thus reflecting the very large prolate elongation of the dinuclear complex during the early stages of fusion. Our theoretical fusion cross sections for both systems agree reasonably well with recent data measured at the Holifield Radioactive Ion Beam Facility. © 2012 American Physical Society.
CRIS-Team Scopus Importer:2023-07-24